A novel algorithm for solving multiplicative mixed-norm regularization problems. (October 2020) - Aucejo, M.; De Smet, O.
Highlights: A novel algorithm for solving mixed-norm regularization is introduced. The proposed algorithm is more robust than the algorithm originally implemented. A detailed comparison of both algorithms is conducted through a numerical experiment. Comparison with ordinary multiplicative regularization is also provided. Abstract: In a paper, recently published in Mechanical Systems and Signal Processing, a multiplicative mixed-norm regularization has been introduced for solving space-frequency force reconstruction problems. Originally, the solution is obtained from an Iteratively Reweighted Least-Squares (IRLS) algorithm. However, as shown in this communication, such an algorithm exhibits a lack of robustness regarding the measurement noise level. For this reason, a novel iterative resolution algorithm, based on the first-order optimality condition, is introduced. From a numerical experiment, it is shown that the proposed algorithm exhibits a better robustness than the IRLS algorithm initially implemented for solving force reconstruction problems in the frequency domain.